Pengaruh Story Telling Berbasis Kearifan Lokal dengan Media Boneka Jari Terhadap Kemampuan Berbicara Anak Usia 4-5 Tahun Di TK Little Muslims - Regina Farhani; Nyimas Muazzomi; Akhmad Fikri Rosyadi (Advances In Education Journal, 2026)
Speaking skills are one of the most important aspects of child development. Some challenges include children's inability to imitate or repeat simple sentences, their inability to use many words to express their desires or tell stories, and their shyness in speaking in public due to a limited vocabulary. These speaking skills must be continuously honed and stimulated, which can be developed through storytelling based on local wisdom and finger puppets. The purpose of this study was to determine the effect of storytelling based on local wisdom and finger puppets on the speaking skills of 4-5-year-old children at Little Muslims Kindergarten. This was an experimental study using a one-group pre-test-posttest design. The population was 57 children. Purposive sampling was used to select 13 children from Class A2. Data collection techniques included observation and documentation. The research instrument used was an observation sheet in accordance with the observation guide. Data analysis techniques included normality tests and homogeneity tests, and hypothesis testing using the t-test. The results of the study showed that Thitung > Ttabel, namely 26,388 > 2.178, so H0 was rejected and Ha was accepted, so it can be concluded that there is an influence of local wisdom-based storytelling with finger puppet media on the speaking ability of children aged 4-5 years at Little Muslims Kindergarten.